Trends in Determinants of Birth Interval based on Data from the Indonesian Demographic Health Survey in 2007, 2012, and 2017 - Nedra Wati Zaly; Mugia Bayu Rahardja; Murtiningsih Murtiningsih (Althea Medical Journal, 2022)
Background: Fertility is the main component of population dynamics that determines the population structure of a country. One method to measure fertility is to analyze the birth interval. This study aimed to identify determinants of birth interval based on the Indonesian Demographic and Health Survey (IDHS) data in 2007, 2012, and 2017.Methods: This study design was descriptive using IDHS data from 2007, 2012, and 2017 with a cross-sectional study design. Samples were mothers who gave birth to their last living child in the last five years.Results: In the IDHS 2007, the birth interval at risk (<24 months) was 11.8%, increased in the 2012 IDHS to 12.1%, and decreased in the 2017 IDHS to 9.8%. In the three-period IDHS, the same determinants of the birth interval were discovered, such as the age of the woman, duration of breastfeeding, use of contraception, the status of the child before the last child, mother’s education level, and wealth quintile. However, in 2007, the sex of the child before the last child and the number of surviving children also influenced the birth interval. In 2017 the number of children who were still alive also affected the birth interval. The most dominant factor influencing the occurrence of short birth intervals after controlling for other variables was the survival status of the previous child.Conclusion: The short birth interval is the most prevalent in the 2012 IDHS. Optimal birth interval has the potential to improve maternal, neonatal, and infant health.